Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes The Evidence from Population-Based Interventions - Handler, Arden; Kennelly, Joan.; Peacock, Nadine; SpringerLink (Online service) (Boston, MA : Springer US, 2011)
Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes: The Evidence from Population-Based Interventions Arden Handler, Joan Kennelly, Nadine Peacock, editors Among women$1 (Bs health concerns, reproductive issues, both prenatal and postpartum, hold particular prominence. Yet despite the many programs dedicated to improving women$1 (Bs reproductive health, maternal and infant morbidity and mortality rates in minority communities remain unchanged$1 (Bor have increased. Confronting this alarming statistic head-on, Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes is the first book systematically examining public health interventions designed toward meeting this important and elusive goal. Its contributors offer the best thinking and practice on this complicated topic, clarifying the relationship between evidence-based medicine and evidence-based public health and its potential for increasing parity, considering interventions in the multiple contexts of women$1 (Bs lives, reviewing the evidence base for each program or initiative featured, and describing methodologies for evaluating interventions. The resulting volume advocates for an integrative lifespan approach, including topics related to: Family planning STI and HIV/AIDS screening and treatment Smoking cessation and reducing exposure to environmental smoke Preconceptional well-woman care Depression screening and treatment Labor/delivery approaches and intrapartum care Emerging prenatal care interventions, from centering pregnancy to doula support For professionals and graduate students in psychiatry, psychology, sociology, women$1 (Bs health, and public health, Reducing Racial/Ethnic Disparities in Reproductive and Perinatal Outcomes reframes a set of ongoing issues and guides the reader toward state-of-the-art solutions.s
Introduction: Challenges in Reducing Disparities in Reproductive and Perinatal Outcomes through Evidence Based Public Health -- Identification and Assessment of the Evidence: Approaches and Guidelines Used in this -- Evidence-Based Public Health: Origins, Assumptions, and Cautions -- Current Approaches to Reducing Premature Births and Implications for Disparity Elimination -- Access to Family Planning and Induced Abortion: Role in Reducing Racial and Ethnic Disparities in Adverse Pregnancy Outcomes -- Preconceptional Health Promotion -- Public Health Interventions for Perinatal HIV and STI Screening in Pregnancy -- Infertility Status and Infertility Treatment: Racial and Ethnic Disparities -- What is the role of Prenatal Care in Reducing Racial and Ethnic Disparities in Pregnancy Outcomes? -- Prenatal Case Management of Pregnant Women: What is The Evidence for Its Contribution to a Reduction of Disparities in Perinatal Outcomes? -- Behavioral Treatment Methods for Pregnant Smokers: The Evidence Base for Prenatal Care Programs and Professional Practice -- Substance use in Pregnancy: The impact of screening and treatment on improving perinatal outcomes and reducing racial and ethnic disparities -- The Evidence for Perinatal Depression Screening and Treatment -- Supplemental Nutrition Programs during Pregnancy and the Early Postnatal Period -- Group Prenatal Care and Doula Care for Pregnant Women -- Contemporary Childbirth in the United States: Interventions and Disparities -- Regionalized Perinatal Care: An Evidence-Based Intervention in Development.
Keywords: Medicine; Maternal and infant welfare; Medicine & Public Health; Maternal and Child Health